PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA PADANG - Anggelina, Ria; Ramayani,, Citra; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACKThis study aims to obtain empirical evidence about the effect of compensation and work environment on employee motivation Regional Water Company ( PDAM ) Jln . H. Agus Salim no.10 Padang . This research is descriptive and associative . The population in this study were 290 employees in PDAM Padang . The method of sample selection in this study is the method of percentage ie 30 % of the population , in order to obtain a sample of 87 employees . The type of data in this study is primary data and secondary data , engineering data analysis using descriptive analysis and inductive analysis conducted through the classical assumption test , multiple linear regression , the coefficient of determination test , t test and F test.The results showed that , first : Compensation significant effect on the motivation of this work is shown with sig 0.024 < Î± 0.05 , meaning that H01 is rejected Ha1 accepted . Second : Significant and positive work environment on work motivation with sig 0.000 < Î± 0.05 , meaning that H02 is rejected Ha2 accepted , third : Compensation and work environment together positive and significant effect on work motivation with sig 0.000 < 0 , 05 , meaning that H03 is rejected and Ha3 accepted . The results of the research the coefficient of determination of the model of this study is the percentage of variable compensation and the effect of work environment on employee motivation PDAM Padang is equal to 46.1 % , while the remaining 53.9 % is influenced by other variables that are not addressed in the study . The results of the study variables simultaneously compensation and work environment has a significant positive effect on the motivation to work with the value of F ( 35.903 ) > Ftable ( 3.10 ) and sig ( 0,000 ) < Î± ( 0.05 ) means Ha3 H03 is rejected and accepted .